Precursor fibers for lignin-based carbon fibers, preparation and use thereof

Ligno fibers are prepared by water-based dry spinning and crosslinking agents are introduced during thermal stabilization and carbonization, which solves the problems of high energy consumption and poor CO2 balance of the existing carbon fiber preparation process, and achieves high-performance and low-cost carbon fiber preparation.

CN119585473APending Publication Date: 2025-03-07HARDWOOD TECH LTD

Patent Information

Application Number
CN202380053595.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-14
Filing Date
2023-07-14
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing carbon fiber preparation process has problems with high energy consumption, poor CO2 balance and the use of toxic solvents, and lignin-based carbon fiber has not yet reached a satisfactory level in terms of mechanical properties and commercial availability.

Method used

Ligno fibers are prepared by water-based dry spinning, water-soluble lignin salts and polyvinylpyrrolidone are used as precursor materials, and crosslinking agents are introduced during thermal stabilization and carbonization to improve the mechanical properties of the fibers.

Benefits of technology

It achieves high carbon yield, low porosity and improved mechanical properties, especially in terms of tensile strength and E modulus, and is economical in process and environmentally friendly, suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005240318490000121
    Figure BDA0005240318490000121
  • Figure BDA0005240318490000131
    Figure BDA0005240318490000131
  • Figure BDA0005240318490000151
    Figure BDA0005240318490000151
Patent Text Reader

Abstract

A precursor fiber of a lignin-based carbon fiber is described, said precursor fiber having a content of a water-soluble lignin salt (A). A particular feature of these precursor fibers is that a water-soluble polyvinyl pyrrolidone or polyvinyl pyrrolidone derivative (B) is included therein. Advantageous methods for the preparation of these precursor fibers and their advantageous use for the preparation of carbon fibers by carbonization and optionally subsequent graphitization are also described.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to methods for making and using lignin precursor fibers dry-spun from water, which precursor fibers can subsequently be converted into carbon fibers.

[0002] Carbon fibers combine outstanding mechanical properties with a low density in the form of fiber composites, which results in a high energy-saving potential. The majority of the carbon fibers produced are based on polyacrylonitrile (PAN) (>95%), which is produced by polymerization of acrylonitrile with a low copolymer ratio. The required acrylonitrile is synthesized from propylene obtained from oil production and ammonia. The production of the precursor fibers is carried out by a special wet spinning process. Due to the high costs of the energy-intensive carbon fiber production, the poor CO2 balance of the entire process and the use of problematic toxic solvents in the wet spinning process, alternative materials and methods have long been sought.

[0003] Lignin has long been investigated as a possible alternative to PAN-based carbon fibers. Decisive for this is the fact that 50 million tons of lignin are produced annually as a byproduct in papermaking and biorefining. Among biopolymers of natural origin, lignin is the second most common after cellulose. About 2% of lignin is used in commercial applications, while the majority is used simply as fuel.

[0004] In addition to its economic significance, lignin has a high carbon yield when carbonized (Fang et al., Manufacture and application of lignin-based carbon fibers (LCFs) and lignin-based carbon nanofibers (LCNFs), Journal of Green Chemistry, 2017, pp. 1794-1827). However, due to the chemical structure, structure and purity, the use of lignin as a precursor material is associated with several difficulties. Lignin is divided into organic solvent lignin, lignin sulfate, alkali lignin and lignin sulfonate by various decomposition methods. Lignin sulfonate is obtained as a by-product in the sulfite process when preparing fiber materials. In this method, the free hydroxyl groups of lignin are replaced by sulfonic acid groups. As a result, lignin becomes soluble in water and can therefore be used in a water-based dry spinning process. Lignin sulfonate with a weight-average molecular weight of up to tens of thousands of g / mol can be produced by the sulfite process, because sulfite decomposition is mostly carried out in an acidic environment and therefore does not destroy the β-O-4 bond in lignin.

[0005] The earliest method for preparing carbonized lignin fibers was disclosed in US 3461082 A (Otani et al.) in 1960. The lignin fibers presented therein can be prepared by means of melt spinning, dry spinning and wet spinning. In the dry spinning process, alkaline lignin, sulfolignin or lignin sulfonate is dissolved in a solvent (such as water, alkaline sodium hydroxide and potassium hydroxide solutions, acidic sulfuric acid solutions or hydrochloric acid solutions). Lignin sulfonate can be spun with the addition of polyvinyl alcohol, PAN or adhesive fibers as plasticizers. Y. Fukuoka of Nippon Kayaku Co. first reported commercial carbon fibers based on lignin sold under the name "Kayacarbon" (see US 3461082 A). DE 2118488 A and US3723609 A describe other co-spinning methods of lignin sulfonate with polyethylene oxide or acrylic acid-acrylamide copolymers as additives, in which fibers with a tensile strength of 0.8 GPa are achieved. Zhang et al. "Carbon", 2014, pp. 626-629 and "Journal of Applied Polymer Science", 2016, pp. 43663 (1-10) studied the dry spinning of acetone of acetylated softwood lignin sulfate and the influence of processing temperature and spinning concentration on the processability of fiber. Microscopic studies show that the microscopic surface has notches and does not have a uniform circular cross-section. This can be explained by means of the rapid evaporation of acetone. The prepared fiber has a strength of 1.04GPa and an E modulus of 52GPa. Since the contamination of the fiber is avoided only by a low heating rate of 0.01°C / min, this method cannot be applied to large-scale production. The stabilization time can be reduced from 40 hours to 4 hours by additional UV irradiation of lignin fibers (see Zhang et al., Carbon Fibers from UV-Assisted Stabilization of Lignin-Based Precursors, "Fibers", 2015, pp. 185-194). However, the mechanical properties were degraded (tensile strength of 900 MPa and E modulus of 34 GPa).

[0006] Jin et al. (Carbon Fibers Derived from Fractionated-Solvated Lignin Precursors for Enhanced Mechanical Performance, ACS Sustainable, Chemistry & Engineering", 2018, pp. 14135-14142) reported lignin fractionated from softwood lignin sulfate with a weight average molecular weight of 28,600 g / mol, which was dry-spun into fibers with a mixture of 85% acetic acid and 15% water. Here, the winding speed was between 20 and 30 m / min. The fiber had a strength of 1.39 GPa and an E modulus of 98 GPa.

[0007] In the 1990s, low-cost lignin fibers were obtained by a simple melt spinning process (Kubo et al., Journal of Polymers and the Environment", 2005, pp. 97-105; Alexy et al., "Polymer", 2000, pp. 4901-4908). According to the current prior art, there are many patents and publications for the preparation of lignin-based carbon fibers. Although the melt spinning process has several advantages over the dry spinning process, such as eliminating the solvent and faster pulling speed. However, due to its amorphous and branched structure, lignin has no melting point and therefore tends to decompose (see Jin et al., "Chemistry & Engineering", 2018, pp. 14135-14142). In addition, the amorphous structure prevents the crystal orientation of the fiber, which may negatively affect the mechanical properties. Therefore, lignin is chemically modified or lignin is spun in a melt spinning process using an additional polymer to offset the poor spinnability. To date, there are no commercially available lignin-based carbon fibers that meet current needs.

[0008] CN 111321487 A describes a method for preparing carbon nanofibers by means of an electrospinning method. These carbon nanofibers should have a graphite structure at the surface and can be used in the fields of energy storage, catalysis and adsorption. In the example of CN 111321487 A, carbon nanofibers are prepared from a mixture of lignin sulfonate and polyvinyl alcohol.

[0009] Starting from the above-mentioned prior art, the present invention is based on the object of specifying advantageous precursor fibers for carbon fibers based on lignin, which overcome the disadvantages described above in connection with the prior art, wherein this should be carried out by an advantageous dry spinning process, wherein water-based dry-spun lignin fibers are thus obtained. These precursor fibers themselves should be convertible advantageously into carbon fibers, which are associated with high carbon yields, low porosity and improved mechanical properties, in particular better tensile strength values ​​and E modulus values.

[0010] That is, the present invention also aims to obtain carbon fibers having outstanding properties in terms of strength and E modulus from the obtained dry-spun precursor fibers by a convenient method.

[0011] The invention achieves this object by means of a precursor fiber for lignin-based carbon fibers, which has a content of a water-soluble lignin salt (A) and a content of a water-soluble polyvinylpyrrolidone or a polyvinylpyrrolidone derivative (B).

[0012] Advantageous designs of these precursor fibers are as follows:

[0013] Advantageously, the water-soluble lignin salt (A) is of the formula LR z (I) means that the residue -Rz represents a sulfonate, phosphate, phosphonate, phosphite, phosphite, phosphite and / or phosphinate residue, wherein the water-soluble lignin salt (A) is used in particular as a lignin sulfonate. It has proven to be advantageous if the cations in the water-soluble lignin salt (A) are sodium, ammonium, calcium and / or magnesium ions, in particular ammonium ions.

[0014] It is also important to pay attention to the weight average molecular weight M of the water-soluble lignin salt (A). W It is useful here that the water-soluble lignin salt (A) has a weight average molecular weight M of about 5,000 to 1,000,000, in particular about 10,000 to 800,000 g / mol. W , and / or the water-soluble polyvinyl pyrrolidone or polyvinyl pyrrolidone derivative (B) has a weight average molecular weight M of about 10,000 to 2,000,000 g / mol, especially about 50,000 to 100,000 g / mol W Within the scope of the invention described here, the molecular weight is determined with the aid of GPC and suitable standards (eg polystyrene).

[0015] In the actual implementation of the invention, it has been shown that the water-soluble polyvinyl pyrrolidone is conveniently present as a homopolymer. It can also be a derivative, in particular a copolymer, wherein the polyvinyl pyrrolidone derivative should essentially correspond to it in terms of physical properties, so that not only the weight-average molecular weight M given above W The range conditions of the invention are consistent with those of the invention and in particular also with the physical parameters specified below. Suitable copolymers are: poly-(1-vinylpyrrolidone-co-vinyl acetate) and poly-(N-vinylcaprolactam-co-N-vinylpyrrolidone). In the copolymers of polyvinylpyrrolidone, the comonomer is contained in a molar amount of 0.1 to 40 mol %, in particular 10 to 30 mol %, expressed as mol %.

[0016] It is particularly preferred that the water-soluble polyvinyl pyrrolidone or polyvinyl pyrrolidone derivative (B) has a softening point of about 100°C to 175°C, in particular about 140°C to 160°C.

[0017] Particularly advantageous effects are achieved with the precursor fibers according to the invention when the precursor fibers according to the invention contain a water-soluble, heat-activatable crosslinking agent (C) in the form of a compound that releases formaldehyde. Advantageously, the heat-activatable crosslinking agent (C) is present as 1,3,5-trioxymethylene, paraformaldehyde, hexamethylenetetramine, dihydroxymethyldihydroxyethyleneurea (DMDHEU), 1,3-bis(hydroxymethyl)imidazolidin-2-one (DMEU) and / or 1,3-bis(hydroxymethyl)urea (DMU).

[0018] Regarding an advantageous design of the precursor fiber of the present invention, the precursor fiber contains about 0.1 to 1 parts by weight, especially about 0.3 to 0.7 parts by weight of water-soluble polyvinyl pyrrolidone or polyvinyl pyrrolidone derivative (B) per 1 part by weight of water-soluble lignin salt (A). As an advantageous quantitative relationship, the precursor fiber contains about 0.01 to 0.3 parts by weight, especially about 0.05 to 0.15 parts by weight of water-soluble crosslinking agent (C) per 1 part by weight of water-soluble lignin salt (A).

[0019] The following detailed method for preparing the precursor fiber of the present invention also falls within the scope of the present invention:

[0020] The subject of the present invention is therefore also a method for producing a precursor fiber of a carbon fiber based on lignin according to the advantageous precursor fiber design presented above. This method is characterized in that an aqueous solution of the water-soluble lignin salt (A) and the water-soluble polyvinyl pyrrolidone or polyvinyl pyrrolidone derivative (B) is prepared, the aqueous solution (D) obtained is dry-spun into monofilaments, thereby forming a precursor fiber of the carbon fiber, and the monofilament is extracted.

[0021] It should be emphasized that the physical properties, in particular the chemical structural characteristics, described in detail here with respect to the precursor fibers of the components in the form of the water-soluble lignin salt (A), the water-soluble polyvinyl pyrrolidone (B) and the water-soluble crosslinking agent also apply.

[0022] Compared to other additional polymers (such as polyvinyl alcohol, see US 3461082 A), the precursor fiber of the present invention can be processed at a higher heating rate, preferably between 5-20K / min, in the stabilization process that will be shown in detail later, due to the inclusion of polyvinyl pyrrolidone. The reason for this is that the thermal behavior of polyvinyl pyrrolidone, in particular its glass transition temperature, is 150°C. Compared to PVA, which has a glass transition temperature of only about 85°C, a higher stabilization temperature can be applied. With polyvinyl pyrrolidone, the fiber can be heated to 150°C without increasing the chain mobility in the amorphous segments of the precursor fiber. This can prevent the precursor fibers from sticking to each other. In addition to obtaining a stable spinning solution by using water-soluble polyvinyl pyrrolidone, this additional polymer can also be dissolved at room temperature.

[0023] The present invention is not essentially restricted when selecting the corresponding water-soluble lignin salt (A). For this purpose, commercially available water-soluble lignin sulfonates, in particular ammonium, calcium, magnesium or sodium lignin sulfonates, are first considered, but other soluble or dispersible water-soluble lignin salts such as phosphates, phosphonates, hypophosphites, phosphites, phosphites or phosphinates are also considered. Advantageously, water-soluble lignin sulfonates with a high molecular weight of more than 30,000 g / mol and a low sugar content of <10%, in particular <3%, are used. By processing high molecular weight water-soluble lignin sulfonates, better mechanical properties, such as strength and E modulus, are achieved.

[0024] A particularly advantageous development of the invention consists in incorporating a water-soluble crosslinker (C) into the aqueous solution (D).

[0025] In the dry spinning method according to the invention, it is preferably possible to proceed as follows: In the dry spinning process, the spinning solution is forced through a defined nozzle hole (100-200 μm diameter) by a spinning pump and dried in a spinning chamber at 40-60° C. The precursor fiber can be wound onto a bobbin with a driven winder. The fiber has a diameter in the range of about 6 μm to 60 μm, preferably 6 to 20 μm, in particular 6 μm to 20 μm and further preferably 6 to 13 μm and particularly preferably 10 to 13 μm. The carbon fibers that can be subsequently produced from the precursor fiber preferably have a diameter of 2 μm to 30 μm, particularly preferably 4 μm to 8 μm.

[0026] To facilitate the spinning process, the aqueous solution (D) is advantageously adjusted to a zero shear viscosity (measured according to DIN 53019-4) of about 50 to 800 Pa.s, preferably about 100 to 600 Pa.s, in particular about 150 to 350 Pa.s, measured at a temperature of 22°C.

[0027] In order to optimize this method, it is also meaningful to concentrate the aqueous solution (D) to increase the zero shear viscosity, especially under vacuum and preferably using a rotary evaporator, until the zero shear viscosity has been adjusted to a zero shear viscosity of about 50 to 800 Pa.s, preferably about 100 to 600 Pa.s, especially about 150 to 350 Pa.s (measured at a temperature of 22° C. according to DIN 53019-4), and to dry-spin the concentrated aqueous solution (E) obtained. The concentration of the aqueous solution (D) is preferably carried out under a vacuum of about 10 to 80 mbar, especially about 45 to 75 mbar. The spinning solution should preferably be free of particles and have no gel properties.

[0028] It has proven to be very advantageous to prepare a mixture in which 1.) about 0.1 to 1 part by weight, in particular about 0.3 to 0.7 part by weight, of water-soluble polyvinyl pyrrolidone or a polyvinyl pyrrolidone derivative (B) is contained per 1 part by weight of the water-soluble lignin salt (A) or 2.) about 0.1 to 1 part by weight, in particular about 0.3 to 0.7 part by weight, of water-soluble polyvinyl pyrrolidone or a polyvinyl pyrrolidone derivative (B) and about 0.01 to 0.3 part by weight, in particular about 0.05 to 0.15 part by weight, of a water-soluble crosslinker (C) is contained per 1 part by weight of the water-soluble lignin salt (A), and the corresponding mixture is dissolved in water and transferred to the aqueous solution (D).

[0029] However, it is also possible to incorporate the water-soluble crosslinking agent (C) into the aqueous solution (E). The quantitative relationship shown between the water-soluble lignin salt (A), the water-soluble polyvinyl pyrrolidone or polyvinyl pyrrolidone derivative (B) and the water-soluble crosslinking agent (C) should also be taken into account. In other words, it is particularly advantageous for the implementation of the present invention to incorporate the water-soluble crosslinking agent (C) into the aqueous solution (D) and / or the aqueous solution (E).

[0030] As already mentioned, it is particularly advantageous for the implementation of the present invention to incorporate the water-soluble crosslinking agent (C) into the aqueous solution (D) and / or the aqueous solution (E). Optionally, the mechanical properties of the fiber can be improved by chemical crosslinking or by the introduction of additional aromatic groups. Therefore, in particular, the water-soluble crosslinking agents (C) indicated above, such as dimethyloldihydroxyethylene urea (DMDHEU), trioxymethylene or urotropine can be used. The water-soluble crosslinking agent (C) contains formaldehyde-releasing compounds, which produce crosslinking of the lignin when thermally activated. The theoretical advantage is that the water-soluble crosslinking agent (C) has already been added to the spinning solution containing the polymer and can be spun together.

[0031] An advantageous development of the method according to the invention is considered in which the concentrated aqueous solution (E) is dry-spun in a spinning chamber at a temperature of about 30 to 100° C., in particular about 40 to 70° C.

[0032] The water content of the aqueous solution (D) has a favorable influence on the successful performance of the process according to the invention. It is considered preferred here that the aqueous solution (D) contains at least about 40% by weight, in particular about 45 to 65% by weight, of water.

[0033] The water-soluble crosslinking agent (C) bonded to the precursor fiber has been described in detail above. The crosslinking agent is present in an activatable form. Therefore, the activation is particularly advantageously initiated when the water-soluble crosslinking agent (C) bonded to the precursor fiber is activated by thermal stabilization of the precursor fiber at a temperature of about 100 to 400° C., in particular about 200 to 300° C., preferably 250° C.+ / -20° C., in particular by oxidative thermal stabilization. The residence time of the precursor fiber in the thermal stabilization is between 10 minutes and 4 hours, preferably between 10 minutes and 60 minutes, particularly preferably between 10 minutes and 40 minutes, depending on the heating rate and the temperature profile.

[0034] A particular object of the invention is to produce advantageous carbon fibers from the precursor fibers described above, optionally with previous thermal stabilization, in particular oxidative thermal stabilization and / or with previous stabilization with high-energy radiation and optionally subsequent graphitization. It is also advantageous to use ultraviolet radiation (UV), vacuum ultraviolet radiation (VUV), electron radiation, X-ray radiation, plasma stabilization and / or gamma radiation as high-energy radiation. This use is therefore taught as a result of the idea of ​​the invention.

[0035] In another aspect, the invention therefore relates to a method for producing carbon fibers from precursor fibers as already given above, wherein the method comprises thermal stabilization, in particular oxidative thermal stabilization and / or stabilization with high-energy radiation and / or plasma stabilization, and subsequent carbonization and optionally subsequent graphitization. Preferably ultraviolet radiation (UV), vacuum ultraviolet radiation (VUV), electron radiation, X-ray radiation and / or gamma radiation are used as high-energy radiation.

[0036] Furthermore, it is advantageous for the specified method if the thermal stabilization of the precursor fiber is carried out in a temperature range of 100° C. to 400° C., in particular 200° C. to 300° C., in particular 250° C.+ / −20° C.

[0037] In the context of the method presented here, the carbonization of the precursor fiber according to the invention is preferably carried out at a temperature between 300° C. and 1800° C., expediently under an inert atmosphere and particularly preferably under a nitrogen atmosphere. It is also advantageous for the carbonization to subject the stabilized precursor fiber to a low temperature spring, in particular in a temperature range of 300° C. to 1200° C., and preferably in a range of 300° C. to 1000° C., and further preferably to 800° C.+ / -50° C. Such a carbonization can be carried out, for example, in a low temperature furnace (LT furnace), wherein such a carbonization is preferably carried out under an inert atmosphere, in particular under a nitrogen atmosphere.

[0038] In a preferred embodiment, the precursor fiber is stretched in a low-temperature furnace, in particular with a stretch factor of between 1% and 35%, preferably at least 2% to 30%, particularly preferably at least 5% to 25%. In this way, a further improvement in the mechanical properties of the fiber can be achieved.

[0039] It is also advantageous if the fibers are subjected to high-temperature carbonization after the low-temperature carbonization, the temperature being adjusted to preferably a range of 1200° C. to 1600° C., more preferably up to 1500° C. and still more preferably up to 1400° C.+ / −50° C. The high-temperature carbonization is expediently carried out in an inert atmosphere.

[0040] The carbon fibers produced from the high-temperature furnace have a diameter in the range of 2 to 30 μm, preferably a diameter of 4 to 8 μm.

[0041] For the graphitization provided within the scope of the method, it is preferred to carry out the graphitization under hot stretching in an inert atmosphere, in particular an argon atmosphere, at a temperature of up to 3000° C. This treatment can further increase the orientation of the carbon fibers and their E modulus by simultaneous hot stretching. The graphitization can conveniently be carried out in a graphitization furnace (ultra-high temperature furnace, UHT furnace).

[0042] In yet another aspect, the invention relates to the use of precursor fibers as already given above for preparing carbon fibers by carbonization, optionally with previous thermal stabilization, in particular oxidative thermal stabilization and / or with previous stabilization with high-energy radiation and / or plasma stabilization, and optionally subsequent graphitization.

[0043] The use of water-soluble polyvinylpyrrolidone as an auxiliary polymer not only improves the spinnability, but also explicitly introduces nitrogen into the carbon fibers, so that the carbon fibers, similar to carbon fibers formed from polyacetonitrile, acquire a nitrogen-containing surface for resin bonding during the production of composite components. In the prior art regarding precursor fibers formed from cellulose or lignin and auxiliary polymers (e.g. PVA), nitrogen atoms must be introduced in a further processing step by plasma processes or chemical functionalization. Oxidative heat stabilization is generally carried out in an oxygen atmosphere up to a final temperature of 100° C. to 400° C. The plastic is heated between 20-0.05 K / min.

[0044] As already shown, the uniqueness of the present invention lies in various advantages: Thus, the present invention allows the production of multifilaments and can be transferred to large-scale equipment. The method of the present invention is economically and ecologically feasible, and its purpose is to achieve environmentally friendly carbon fibers at low production costs. In the production of low-cost carbon fibers, the carbon yield after carbonization plays an important role. Therefore, there is a great interest in keeping the lignin proportion in the precursor fiber as high as possible. The precursor fiber therefore preferably has a lignin content of at least 70% by weight, wherein 80% by weight has also been demonstrated. The present invention therefore relates to a continuous dry spinning method of preferably water-soluble lignin sulfonates and polyvinyl pyrrolidone in the case of water as solvent.

[0045] Polyvinyl pyrrolidone in particular enables high spinning speeds in the range of at least 75 m / min to 100 m / min, since the more brittle and amorphous spinning solution produced based on lignin is stabilized. Polyvinyl pyrrolidone in particular enables a simplified orientation of the lignin polymer in the fiber direction and reduces brittleness, thereby making handling, in particular winding, etc. easier.

[0046] The polyvinyl pyrrolidone or polyvinyl pyrrolidone derivative (B) added to the spinning solution also allows very high stabilization speeds of 10-20 m / min, which are hardly achievable in the prior art. This significantly saves energy and costs in the preparation of the carbon fibers of the invention. The invention will be explained in more detail below with the aid of examples:

[0047] Embodiment 1:

[0048] (Preparation of a spinning solution having 1 part by weight of ammonium lignin sulfonate (cork) and 0.43 parts by weight of polyvinyl pyrrolidone and a dry spinning process)

[0049] The mixture according to the invention is dissolved in water to prepare a spinning solution. 500 g of the mixture means one part by weight (350 g) of ammonium lignin sulfonate (cork) and 0.43 parts by weight (150 g) of polyvinyl pyrrolidone (PVP K30 from Sigma Aldrich) with a weight average molecular weight of 50,000 g / mol, which is dissolved in 1.4 l of water under stirring. After 30 minutes of stirring at room temperature, the solution is homogenized. Possible residual particles are removed by filtration. The spinning solution obtained is concentrated on a rotary evaporator in a vacuum until a zero shear viscosity of 229 Pa.s is obtained at 22 ° C. Rheological measurements are carried out by a Physica MCR 301 rheometer from Anton Paar, which has a plate-plate geometry with a plate diameter of 25 mm and a gap distance of 0.5 mm.

[0050] The dry spinning process was carried out on a pilot scale with a porous nozzle. The spinning nozzle had a diameter of 100 μm and 90 filaments. The worm speed was 7.6 rpm. The spinning temperature was 22° C. The fibers were dried in air at a temperature between 40 and 50° C. in the spinning chamber. The fibers were wound up at a winding speed of 80 m / min and stored under constant climatic conditions (23° C., 40% relative humidity). After the dry spinning process, the moisture content of the fibers was between 8 and 12% by weight. The determination was carried out by means of Karl-Fischer titration at 140° C.

[0051] Embodiment 2:

[0052] (Preparation of a spinning solution having 1 part by weight of ammonium lignin sulfonate (hardwood) and 0.43 parts by weight of polyvinyl pyrrolidone and a dry spinning process)

[0053] Example 2 was carried out, except that ammonium ligninsulfonate (hardwood) was used instead of ammonium ligninsulfonate (softwood). Thus, similar to the procedure described in Example 1, 500 g of a mixture consisting of 1 part by weight (350 g) of ammonium ligninsulfonate (hardwood) and 0.43 parts by weight (150 g) of polyvinylpyrrolidone with a weight-average molecular weight of 50,000 g / mol (PVP K30 from Sigma Aldrich) were mixed in 1.4 l of water. After 30 minutes of stirring at room temperature, the solution was homogenized. Any remaining particles were removed by filtration. The spinning solution obtained was concentrated on a rotary evaporator in vacuo until a zero shear viscosity of 282 Pa.s at 22° C. was obtained. The rheological measurements were carried out by means of a Physica MCR 301 rheometer from Anton Paar, which had a plate-plate geometry with a plate diameter of 25 mm and a gap distance of 0.5 mm.

[0054] The dry spinning process was carried out on a pilot scale with a porous nozzle. The spinning nozzle had a diameter of 100 μm and 90 filaments. The worm speed was 7.6 rpm and the spinning temperature was 22° C. The fibers were dried in air at a temperature between 45 and 55° C. in the spinning chamber. The fibers were wound up at a winding speed of 90 m / min and stored under constant climate conditions (23° C., 40% relative humidity).

[0055] After the dry spinning process, the moisture content of the fibers was between 8 and 12% by weight, as determined by Karl-Fischer titration at 140°C.

[0056] Embodiment 3:

[0057] (Preparation of a spinning solution having 60-80 wt% lignin sulfonate and 40-20 wt% polyvinyl pyrrolidone and a dry spinning process)

[0058] 60-80 wt. % lignin sulfonate and 40-20 wt. % polyvinyl pyrrolidone are dissolved in water and concentrated using a rotary evaporator. The water content in the spinning solution obtained is 44-55 wt. % and the zero shear viscosity is 170-500 Pa.s. The spinning nozzle comprises 90 to 250 nozzle holes with a diameter of 100 μm, from which rovings formed by 90 to 250 filaments are produced. The maximum spinning speed is between 75 and 100 m / min, wherein the spinning chamber is heated to between 40° C. and 70° C. Part of the spun coils are plied 4 times to form plied rovings (1k filaments) under controlled tension for continuous carbonization.

[0059] Embodiment 4:

[0060] (A spinning solution having 1 part by weight of ammonium lignin sulfonate, 0.36 parts by weight of polyvinyl pyrrolidone, and 0.07 parts by weight of a crosslinking agent (DMDHEU) was prepared and a dry spinning process was performed)

[0061] 500 g of the mixture means one part by weight (350 g) of ammonium ligninsulfonate (cork), 0.36 part by weight (125 g) of polyvinylpyrrolidone with a weight average molecular weight of 50,000 g / mol (PVP K30 from Sigma Aldrich) and 0.07 part by weight (25 g) of a crosslinker (DMDHEU), which are dissolved in 1.4 l of water with stirring. The process measures of Example 1 are therefore repeated with the following changes, wherein the amount of polyvinylpyrrolidone is reduced from 0.43 part by weight to 0.36 part by weight and 0.07 part by weight of a crosslinker (DMDHEU) is additionally introduced into the aqueous solution.

[0062] After 30 minutes of stirring at room temperature, the solution is homogenized. Any remaining particles are removed by filtration. After concentration by evaporating water in a vacuum, the zero shear viscosity of the spinning solution is adjusted to 200-300 Pa-s (measured at a temperature of 22° C. according to DIN 53019-4). The solution is spun through a porous nozzle (100 μm) in a dry spinning process and wound up at 80-90 m / min.

[0063] Table 1: Dry spinning experiments with different mixing ratios

[0064]

[0065] *Note: η0 is zero shear viscosity

[0066] Embodiment 5: (Preparation of carbon fiber: discontinuous)

[0067] The precursor fibers obtained according to the above examples 1 to 3 were discontinuously stabilized in a muffle furnace at up to 250° C. The heating rate varied between 0.5 K / min and 20 K / min, wherein even at 20 K / min the fibers did not stick.

[0068] The tensile strength and E modulus of the precursor fibers were determined using a Favimat from Textechno. For this purpose, a monofilament with a spinning length of 12 mm was clamped between two clamps and its count was determined by measuring the resonant frequency. The test speed for the measurement was 1 mm / min. At least 20 valid measurements were used to calculate the average value. The fiber diameter of the monofilament was determined by means of a scanning electron microscope (REM).

[0069] The stabilized precursor fibers had a tensile strength of 8-10 cN / tex and an E modulus of 400 cN / tex.

[0070] The subsequent carbonization was carried out discontinuously in a batch furnace at between 1000° C. and 1400° C. in a nitrogen atmosphere. The heating rate was 10 K / min. The carbonized fibers had a diameter of between 10 and 14 μm (REM photograph). After cooling, carbon fibers were present with a carbon yield of 45%. Table 2 below shows by way of example the carbon fiber values ​​achieved. In the case of continuous carbonization, much higher values ​​of the mechanical characteristics should be assumed, since only in this case can the precursor be stretched.

[0071] Table 2: Mechanical properties after carbonization at 1400°C

[0072]

[0073] Embodiment 6:

[0074] The precursor fibers obtained according to Example 3 above were first plied under controlled tension to form a 1 k roving and subsequently stabilized discontinuously in a muffle furnace at up to 250° C. A heating rate of 1 K / min was used with a dwell time of 4 hours.

[0075] The subsequent continuous carbonization is carried out in a temperature range of 300° C. to 750° C. in an LT furnace and in a nitrogen atmosphere until different carbonization final temperatures in an HT furnace. The mechanical characteristic values ​​of the individual carbon fiber filaments produced in the continuous carbonization process at different maximum temperatures of 1000° C. to 1600° C. in a high-temperature furnace are shown in the table below. It can be seen that the highest tensile strength can be achieved in the range between 1200-1600° C. and the optimal value is 1400° C.

[0076] Table 3: Mechanical properties after continuous carbonization at different maximum temperatures in the HT furnace.

[0077] T-HAT maximum value [℃] 1000 1200 1400 1500 1600 Tensile strength[GPa] 0.7±0.2 0.96±0.2 1.0±0.3 0.99±0.3 0.8±0.2 Modulus E1[GPa] 55±12 68±12 74±20 66±23 47±10 Elongation [%] 1.2±0.3 1.5±0.2 1.4±0.4 1.6±0.4 1.8±0.4 Count [dtex] 2.4±0.5 2.0±0.2 2.0±0.4 1.8±0.3 2.1±0.3 Measurements 30 30 30 30 30

[0078] The defect bands (D1 band, 1340 cm -1 ) and graphite band (G band, 1590cm -1 The intensity ratio of the carbon fibers (ID / IG) depends on the carbonization temperature and gives conclusions about the defects in the graphite structure. The smaller the ID / IG ratio, the smaller the number of defects in the carbon structure. As the maximum temperature during carbonization (coking temperature) increases, the ID / IG ratio decreases from 9.5 to 2.3 (-76%), which is shown in Table 4. The spectra and data of carbon fibers prepared at different maximum temperatures of 1000°C to 1600°C in a high-temperature furnace were obtained and calculated.

[0079] Table 4: ID / IG values ​​of carbon fibers produced by continuous carbonization at different maximum carbonization temperatures

[0080] Sample ID Maximum temperature [℃] <![CDATA[I D / I G ]]> CF1000 1000 9.5 CF1200 1200 4.0 CF1400 1400 3.3 CF1600 1600 2.3

[0081] Example 7

[0082] (Continuous preparation of carbon fibers with various tensile moduli)

[0083] Analogously to the process described above (Example 3), fibers (60 wt. % ligninsulfonate hardwood / 40 wt. % PVP) were spun from 250 filaments and plied to 1K roving and stabilized in a drying oven at up to 250° C. with 1K / min (4 h residence time). The fibers were subsequently wound onto bobbins and carbonized in an LT furnace at 1% and 5% elongation factors (300° C. to 750° C.). The mechanical properties of the fibers are summarized in Table 6. Here, an increased elongation factor results in an increase in the fiber values. The average values ​​for the tensile strength at 5% elongation were 1.4 GPa, the E1 modulus was 104 GPa and the elongation was 1.3%.

[0084] Table 5: Mechanical properties after continuous carbonization at different tensions

[0085]

[0086] The crystallite sizes (L a , L c ), layer plane spacing (d 002 ) and the number of stacked layers (N C ), obtained and calculated by means of wide-angle X-ray scattering of the corresponding carbon fibers at different stretching coefficients at 1400°C. It can be seen that due to the 5% stretching, the crystallite size L a and L c increases, the crystallite grows, and the inter-layer spacing d 002 It is particularly advantageous that the orientation increases with the increase in stretch absorption.

[0087] Table 7: WAXS measurements or orientation of lignin-based CFs with 0-5% stretch factor

[0088]

[0089] In addition, two-dimensional wide-angle X-ray scattering images of carbon fibers with different stretch coefficients were recorded. It can be seen that the more obvious the sickle shape is, the greater the stretching at 1400°C.

[0090] Embodiment 8:

[0091] (Comparative Example / Spinning solution with pure lignin sulfonate without polyvinyl pyrrolidone)

[0092] 500 g of ammonium ligninsulfonate (cork) were dissolved in 1.4 l of water. After 30 minutes of stirring at room temperature, the solution was homogenized. Any remaining particles were removed by filtration. After concentration by evaporating the water in a vacuum, the viscosity of the spinning solution was adjusted. The spinning solution could not be spun because there was not enough yarn stretching capacity.

Claims

1. A precursor fiber of lignin-based carbon fibers, the precursor fiber having a certain content of a water-soluble lignin salt (A) and a certain content of a water-soluble polyvinyl pyrrolidone or a polyvinyl pyrrolidone derivative (B).

2. The precursor fiber according to claim 1, characterized in that The water-soluble lignin salt (A) is represented by the formula LR z (I) represents wherein the residue -Rz represents a sulfonate, phosphate, phosphonate, phosphinate, phosphite, phosphite, phosphite and / or phosphinate residue.

3. The precursor fiber according to claim 2, characterized in that The water-soluble lignin salt (A) is present as lignin sulfonate.

4. Precursor fiber according to at least one of the preceding claims, characterized in that The cations in the water-soluble lignin salt (A) are sodium ions, ammonium ions, calcium ions and / or magnesium ions, especially ammonium ions.

5. Precursor fiber according to at least one of the preceding claims, characterized in that The water-soluble lignin salt (A) has a weight average molecular weight M of about 5,000 to 1,000,000, especially about 10,000 to 800,000 g / mol. W , and / or the water-soluble polyvinyl pyrrolidone or polyvinyl pyrrolidone derivative (B) has a weight average molecular weight M of about 10,000 to 2,000,000 g / mol, in particular about 50,000 to 200,000 g / mol, and particularly preferably about 50,000 to 100,000 g / mol W .

6. Precursor fiber according to at least one of the preceding claims, characterized in that The water-soluble polyvinyl pyrrolidone is present as a homopolymer.

7. Precursor fiber according to at least one of the preceding claims, characterized in that The water-soluble polyvinyl pyrrolidone or polyvinyl pyrrolidone derivative (B) has a softening point of about 100 to 175°C, in particular about 140 to 160°C.

8. Precursor fiber according to at least one of the preceding claims, characterized in that The precursor fibers comprise a water-soluble, heat-activatable crosslinking agent (C) in the form of a formaldehyde-releasing compound.

9. The precursor fiber according to claim 8, characterized in that The heat-activatable crosslinker (C) is present as 1,3,5-trioxane, paraformaldehyde, hexamethylenetetramine, dimethyloldihydroxyethyleneurea (DMDHEU), 1,3-bis(hydroxymethyl)imidazolidin-2-one (DMEU) and / or 1,3-bis(hydroxymethyl)urea (DMU).

10. Precursor fiber according to at least one of the preceding claims, characterized in that In the precursor fiber, about 0.1 to 1 parts by weight, in particular about 0.3 to 0.7 parts by weight of water-soluble polyvinyl pyrrolidone or a polyvinyl pyrrolidone derivative (B) is contained per 1 part by weight of the water-soluble lignin salt (A).

11. Precursor fiber according to at least one of claims 8 to 10, characterized in that The water-soluble crosslinking agent (C) is contained in an amount of about 0.01 to 0.3 parts by weight, particularly about 0.05 to 0.15 parts by weight, based on 1 part by weight of the water-soluble lignin salt (A).

12. Method for producing precursor fibers for lignin-based carbon fibers according to at least one of claims 1 to 11, characterized in that An aqueous solution of the water-soluble lignin salt (A) and the water-soluble polyvinyl pyrrolidone or polyvinyl pyrrolidone derivative (B) is prepared, the obtained aqueous solution (D) is dry-spun into monofilaments to form precursor fibers of carbon fibers, and the monofilaments are drawn out.

13. The method according to claim 12, characterized in that A water-soluble crosslinking agent (C) is incorporated into the aqueous solution (D).

14. The method according to claim 12 or 13, characterized in that The aqueous solution (D) is adjusted to a zero shear viscosity of about 50 to 800 Pa.s, preferably about 100 to 600 Pa.s, in particular about 150 to 350 Pa.s (measured at a temperature of 22° C. according to DIN 53019-4).

15. The method according to claim 14, characterized in that The aqueous solution (D) is concentrated, in particular under vacuum, to increase the zero shear viscosity until the zero shear viscosity has been adjusted to a zero shear viscosity of about 50 to 800 Pa.s, preferably about 100 to 600 Pa.s, in particular about 150 to 350 Pa.s (measured at a temperature of 22° C. according to DIN 53019-4), and the concentrated aqueous solution (E) is dry-spun.

16. The method according to any one of claims 12 to 15, characterized in that A mixture is prepared in which 1.) about 0.1 to 1 part by weight, in particular about 0.3 to 0.7 part by weight, of water-soluble polyvinyl pyrrolidone or a polyvinyl pyrrolidone derivative (B) is contained per 1 part by weight of a water-soluble lignin salt (A) or 2.) about 0.1 to 1 part by weight, in particular about 0.3 to 0.7 part by weight, of a water-soluble polyvinyl pyrrolidone or a polyvinyl pyrrolidone derivative (B) is contained per 1 part by weight of a water-soluble lignin salt (A) and about 0.01 to 0.3 part by weight, in particular about 0.05 to 0.15 part by weight, of a water-soluble crosslinker (C) is contained per 1 part by weight of a water-soluble lignin salt (A), and the corresponding mixture is dissolved in water and transferred to an aqueous solution (D).

17. The method according to claim 15 or 16, characterized in that The concentration of the aqueous solution (D) is carried out under a vacuum of about 10 to 80 mbar, in particular about 45 to 75 mbar.

18. The method according to claim 16 or 17, characterized in that The concentrated aqueous solution (E) is dry-spun in a spinning chamber at a temperature of about 30°C to 100°C, in particular about 40°C to 70°C.

19. The method according to at least one of claims 12 to 18, characterized in that The aqueous solution (D) comprises at least about 40% by weight, in particular about 45 to 65% by weight, of water.

20. The method according to at least one of claims 13 to 19, characterized in that The water-soluble crosslinking agent (C) incorporated into the precursor fiber is activated by heat stabilizing the precursor fiber at a temperature of about 100 to 400°C, especially about 200 to 300°C, especially by oxidative heat stabilization.

21. Method for producing carbon fibers from precursor fibers according to at least one of claims 1 to 11, characterized in that Thermal stabilization, in particular oxidative thermal stabilization and / or stabilization with high-energy radiation and / or plasma stabilization, and subsequent carbonization and optionally subsequent graphitization are carried out to produce the carbon fibers.

22. The method according to claim 21, characterized in that Ultraviolet radiation (UV), vacuum ultraviolet radiation (VUV), electron radiation, X-ray radiation and / or gamma radiation are used as high-energy radiation.

23. The method according to claim 21 or claim 22, characterized in that The thermal stabilization of the precursor fiber is carried out in a temperature range of 100°C to 400°C, in particular 200°C to 300°C, in particular at 250°C+ / -20°C.

24. The method according to any one of claims 21 to 23, characterized in that The stabilized precursor fibers are subjected to low-temperature carbonization in a temperature range of 300°C to 1200°C, in particular in a range of 300°C to 1000°C.

25. The method according to claim 24, characterized in that The precursor fiber is preferably stretched in a low-temperature furnace with a stretch factor of between 1% and 35%, preferably at least 2% to 30%, particularly preferably at least 5% to 25%, in order to improve the mechanical properties.

26. The method according to claim 24 or 25, characterized in that The fibers obtained by the low-temperature carbonization are preferably subjected to a high-temperature carbonization in a temperature range of 1200° C. to 1600° C., further preferably up to 1500° C. and even more preferably at 1400° C.+ / −50° C., especially in an inert atmosphere.

27. The method according to claim 26, characterized in that The fibers obtained by the high-temperature carbonization are graphitized under hot stretching in an inert atmosphere, in particular an argon atmosphere, at a temperature of up to 3000° C.

28. Use of a precursor fiber according to at least one of claims 1 to 11 for producing carbon fibers by carbonization, optionally with previous thermal stabilization, in particular oxidative thermal stabilization and / or with previous stabilization with high-energy radiation and / or plasma stabilization, and optionally subsequent graphitization.

Citation Information

Patent Citations

  • Preparation method of carbon nanofiber with graphene structure on surface

    CN111321487A

  • DE2118488A1

  • Method for producing carbonized lignin fiber

    US3461082A

  • Process for the production of carbon fibers

    US3723609A

Cited By

  • Production process of bio-based high-modulus carbon fiber and prepared bio-based high-modulus carbon fiber

    CN120041975A